МЕКТЕП ОҚЫЎШЫЛАРЫНЫҢ ҲУҚЫҚЫЙ МӘДЕНИЯТЫН ҚӘЛИПЛЕСТИРИЎДЕ ҲУҚЫҚ ПӘНЛЕРИН ОҚЫТЫЎДЫҢ ӘҲМИЙЕТИ - Арзиева, Б.И. (ILIM hám JÁMIYET, 2020)
This article discusses the role of legal science in school in the formation of the legal culture of school-age children, as well as the importance of the normative documents adopted in our country in raising the legal culture and legal education of young people in our country